PENGARUH PENAMBAHAN SERAT LIMBAH KERAJINAN ROTAN TERHADAP KUAT TEKAN MORTAR GEOPOLIMER ABU CANGKANG SAWIT - Nasrullah, Abdi (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2025)
This research discusses utilization of palm kernel shell ash from residual boiler fuel in tea processingtea processing as a substitute for cement, utilization of leftover shavings from rattan handicraftsas fiber. The purpose of this study was to determine the effect of fiberon the compressive strength of palm kernel shell ash geopolymer motar. The research method used is the experimental method using alkaline activators NaOH and Na2SiO3 with the ratio of NaOH to Na2SiO3. Na2SiO3 with a ratio of 1:1 and a molarity of 16 M, the percentage of fiber addition used was 0%, 0.5%, and 1% of the weight of the precursor and a fiber length of 2.5%. and fiber length of 2 cm. All specimens were tested for compressive strengthat the age of 3, 7, 14, 21, and 28 days. The results of the research that has been doneobtained that the highest compressive strength occurred at the age of 28 days with a percentage ofpercentage of 0% fiber at 7.3 Mpa. While for a percentage of 0.5% fiber of 5.3 Mpaand for 1% fiber percentage of 4.8 Mpa. Based on this researchshows that the addition of rattan craft waste fibers in the geopolymer mortar mixture, the compressive strength decreases. mortar mix, the compressive strength results decreased due to the addition of rattan craft waste fibers to the geopolymer mortar. fiber in the geopolymer mortar resulted in the density level of the mortar decreasing, resulting in shrinkage. mortar decreases, resulting in shrinkage of the fibers, and making the volume of the mortar have voids that affect the compressive strength. mortar has voids that affect the compressive strength of the mortar.